2018
DOI: 10.3390/ijms19113535
|View full text |Cite
|
Sign up to set email alerts
|

The Expected and Unexpected Roles of Nitrate Transporters in Plant Abiotic Stress Resistance and Their Regulation

Abstract: Nitrate transporters are primarily responsible for absorption of nitrate from soil and nitrate translocation among different parts of plants. They deliver nitrate to where it is needed. However, recent studies have revealed that nitrate transporters are extensively involved in coping with adverse environmental conditions besides limited nitrate/nitrogen availability. In this review, we describe the functions of the nitrate transporters related to abiotic stresses and their regulation. The expected and unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 81 publications
(131 reference statements)
0
48
0
Order By: Relevance
“…In our opinion, CAL2 possesses Cd chelation activity, and may enhance Cd tolerance when heterologously expressed in Arabidopsis; however, our experimental data in this study (Supplementary Figure S3A) suggest that Arabidopsis plants heterologously expressing CAL2 exhibit a Cd-sensitive phenotype. This is an unexpected phenomenon, which might be due to the side effects caused by heterologous overexpression of the CAL2 gene driven by the 35S promoter, high Cd accumulation in shoots of CAL2-overexpression lines (Figure 4A), or Cd/Na stress mediating nitrate allocation to roots, which promotes stress tolerance (Li et al, 2010;Zhang et al, 2014Zhang et al, , 2018. Our results indicate that CAL2 may negatively regulate the root/shoot nitrate ratio under Cd stress conditions to decrease Cd tolerance in Arabidopsis (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, CAL2 possesses Cd chelation activity, and may enhance Cd tolerance when heterologously expressed in Arabidopsis; however, our experimental data in this study (Supplementary Figure S3A) suggest that Arabidopsis plants heterologously expressing CAL2 exhibit a Cd-sensitive phenotype. This is an unexpected phenomenon, which might be due to the side effects caused by heterologous overexpression of the CAL2 gene driven by the 35S promoter, high Cd accumulation in shoots of CAL2-overexpression lines (Figure 4A), or Cd/Na stress mediating nitrate allocation to roots, which promotes stress tolerance (Li et al, 2010;Zhang et al, 2014Zhang et al, , 2018. Our results indicate that CAL2 may negatively regulate the root/shoot nitrate ratio under Cd stress conditions to decrease Cd tolerance in Arabidopsis (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…However, when 4-week-old hydroponically grown 35S:CAL2-mRFP transgenic and wild-type Col-0 plants were exposed to 20 µM Cd for 3 days, the TYD-6 and TYD-7 lines showed greater Cd sensitivity than the wild-type control plants (Supplementary Figure S3A). Previous research revealed that Cd/Na stress influences nitrate allocation to the roots, which is regulated by the nitrate transporters, NRT1.8 and NRT1.5, and functions in promoting stress tolerance (Li et al, 2010;Zhang et al, 2014Zhang et al, , 2018. To investigate the potential mechanisms of cadmium sensitivity, nitrate concentrations in A. thaliana FIGURE 5 | Ectopic expression of CAL2 increased Cd allocation to shoot in Arabidopsis.…”
Section: Heterologous Expression Of Cal2mentioning
confidence: 99%
“…This could also be one of the reasons for the reduced nitrate levels observed in the present study at 7 dpi in the roots of A. thaliana infected with H. schachtii . Another explanation may be as a result from their intensive root‐to‐shoot transport, where carbon skeletons, energy, and reducing power derived from photosynthesis are easily available and allow the conversion of inorganic N to the organic form (Labudda et al , ; Zhang et al , ). Indeed, their increased content in shoots of infected plants was only recorded at this time point.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed mechanism of this root-shoot translocation of K + still remains ambiguous, although transporters which affect the shoot/root ratio of K + might contribute, such as KUP7 (Han et al, 2016) and OsHAK16 from rice (Feng et al, 2019). Likewise, the identity of the transporters responsible for the retrieval of anions from the xylem remains unclear too, albeit several transporters such as NRT1.8/NPF7.2 (Li et al, 2010;Fan et al, 2017;Zhang et al, 2018) and Cation/ Chloride Cotransporters (CCCs) (Li et al, 2017a) have been suggested.…”
Section: Calcium-dependent Import Of Potassium and Anions-regulator Omentioning
confidence: 99%